Ferrocene and ferrocenium inclusion compounds with cucurbiturils: a study of metal atom dynamics probed by Mössbauer spectroscopy. Issue 32 (2nd August 2017) - Magalhães, Clara I. R.; Gomes, Ana C.; Lopes, André D.; Gonçalves, Isabel S.; Pillinger, Martyn; Jin, Eunyoung; Kim, Ikjin; Ko, Young Ho; Kim, Kimoon; Nowik, Israel; Herber, Rolfe H.
Abstract : This study shows that Mössbauer spectroscopy is a sensitive probe of host–guest interactions and molecular motion in cucurbituril–ferrocene/ferrocenium complexes. Abstract : Temperature-dependent 57 Fe Mössbauer effect (ME) spectroscopic studies were carried out on ferrocene (Fc), 1, 1′-dimethylferrocene (1, 1′(CH3 )2 Fc) and ferrocenium hexafluorophosphate (FcPF6 ) guest species in cucurbit[ n ]uril ( n = 7, 8) inclusion complexes. The solid inclusion complexes were isolated by freeze-drying of dilute aqueous solutions and/or microwave-assisted precipitation from concentrated mixtures. The presence of genuine 1 : 1 (host : guest) inclusion complexes in the isolated solids was supported by liquid-state 1 H and solid-state 13 C 1 H MAS NMR, elemental and thermogravimetric analyses, powder X-ray diffraction, FTIR spectroscopy, and diffuse reflectance UV-Vis spectroscopy. The ME spectra of the complexes CB7·Fc and CB7·1, 1′(CH3 )2 Fc consist of well-resolved doublets with hyperfine parameters (isomer shift and quadrupole splitting at 90 K) and temperature-dependent recoil-free fraction data that are very similar to those for the neat parent compounds, Fc and 1, 1′(CH3 )2 Fc, suggesting that the organometallic guest molecules do not interact significantly with the host environment over the experimental temperature range. The ME spectra for CB7·FcPF6 and CB8·FcPF6 consist of a major broad line resonance attributed to a paramagnetic Fe III site. From the temperature-dependence of the recoil-free fraction it is evident that the charged guest species in these systems interact with the host environment significantly more strongly than was observed in the case of the neutral guest species, Fc and 1, 1′(CH3 )2 Fc. Moreover, the ME data indicate that the vibrational amplitude of the ferrocenium guest molecule is significantly larger in the CB8 host molecule than in the CB7 homologue, as expected on the basis of the different cavity sizes.